Cohesion in the Mapalus Rumah Culture as a Model for Women’s Empowerment Management - Treesje Imran; Erna Ngala; Patricia Jeaneth Cyntia Kojongian; Jemmy Sondakh (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The increasingly humanistic development of Human Resource Management (HRM) requires the integration of social and cultural values into organizational practices. However, local culture is often perceived as limiting women’s participation and gender equality. This study aims to analyze cohesion within the Mapalus Rumah culture and explore its potential as a local wisdom–based model for women’s empowerment in HRM. The novelty of this study lies in positioning Mapalus Rumah culture as a culturally grounded HRM model that integrates women’s participation, social cohesion, and collective empowerment into modern organizational management. This research employed a qualitative approach with an exploratory descriptive design. Sixteen informants were selected through purposive sampling, consisting of 12 women actively involved in Mapalus Rumah activities and 4 supporting informants. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the interactive model of Miles and Huberman with triangulation to ensure validity. The findings show that cohesion in Mapalus Rumah culture is built through continuous social interaction, mutual trust, open communication, and collective commitment. Women play strategic roles as initiators, decision-makers, and social agents within the community. Strong patterns of emotional support, solidarity, and resource exchange among women also contribute to strengthening individual capacity and collective social resilience. These findings indicate that local culture can function as an inclusive space that supports contextual gender equality, understood as gender relations that adapt to local social and cultural contexts while still promoting equal participation and opportunities for women. This study concludes that Mapalus Rumah culture has strong potential as a culturally based management model relevant to modern organizations. The integration of cohesion, participation, solidarity, and community-based support into HRM practices can serve as an effective and sustainable strategy for women’s empowerment, employee engagement, and socially adaptive organizational development in the modernization era.